The perceptions of newly qualified nurses of their readiness to practice in an academic hospital in Gauteng - Shongwe, Sithembile Siphiwe (My University, 2018)
Background: The literature reveals that newly qualified nurses are faced with challenges during their first year of professional practice. These challenges are attributed to the nursing education programme’s inability to adequately equip them with the necessary skills for the role, lack of support during the transition to practice and a negative working environment. Purpose: The purpose of the study was to explore the perceptions of newly qualified nurses of their readiness to practice in an academic hospital in Gauteng. Methodology: a qualitative, exploratory research design, using semi-structured interviews was used to guide the study. Sixteen (16) newly qualified nurses (NQNs) working in an academic hospital in Johannesburg were interviewed. The interviews were digitally recorded and analysed using Braun and Clarke’s phases of thematic analysis. Results: The data were analysed under four themes: the transition from education to practice, support, working environment and settling in. The newly qualified nurses felt that their educational programme concentrated more on theoretical than practical knowledge. As a result, they were not ready for practice and expressed an inability to handle their professional responsibilities. Adapting to the professional role was further compounded by the lack of support, as indicated by complaints about the quality and the duration of on-the-job orientation, lack of supervision from some of the operational managers and senior nursing staff. The shortage of material and human resources was also cited as hindrances. However, their initial feelings of being overwhelmed gradually dissipated resulting in role acceptance and finally growth. Recommendations: The researcher suggests that both theory and practical learning should be given equal value to avoid over prioritisation of one educational aspect to the other. The nursing education delivery systems and the healthcare delivery system must be restructured to facilitate a seamless transition of newly qualified nurses to practice.
A research report submitted to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Nursing (Nursing Education) Johannesburg, 2018.
Keywords: Newly Qualified Nurses; Tertiary Care Centers (Academic Hospital); Professional Practice